“An Artist With Trauma” in Search of Identity: The Postmodernist Options in Ukrainian and Turkish Literatures - Halchuk, Oksana (Respectus Philologicus, 2023)
The article examines the typological features of the image of an artist with trauma and its correlation with the issue of identity. The subjet matter for the analysis are the novels My Name is Red by O. Pamuk and The City with Chimeras by O. Ilchenko. The article utilises historical-literary, comparative, and mythopoetic research methods and studies of traumatic writing and identity problems. The article defines the characteristic features of the image of a traumatised artist, such as the artist’s stay in a traumatic situation of creative and personal crisis, fanatical worship of the idea of serving Beauty with a dominance of the aesthetic over the moral, willingness to justify death as a form of convincing opponents; the presence of a physical injury. The article also substantiates the expediency of Medusa Gorgona’s image as a mythos-archetypal counterpart of this image. The results of the comparative analysis prove that an artist with trauma is relevant primarily for the artistic understanding of the post-colonial experience as a type of trauma. Their heroes are in search of identity. It becomes their successful or unsuccessful attempt to overcome the trauma through creativity.